Menuju Ketahanan Pangan Indonesia Berkelanjutan 2025: Tantangan dan Penanganannya - Achmad Suryana (Forum penelitian Agro Ekonomi, 2014)
EnglishProblems and challenges in achieving sustainable Indonesian food security are multi-dimensional including economic, social, political, and environmental aspects. Identification of those problems and challenges can be approached through food supply and demand analysis. From supply side, those challenges, among others, are a stiff competition in the use of natural resources, impacts of global climate change, and the dominance of small-scale farmers in food farming. From demand side, several challenges are the existence of high population growth and its dynamic characteristics, change in food consumers' preference, and competition in demand for food commodities as human consumption, feed, and energy uses. This paper aims to review current condition of Indonesian food security, to analyze challenges faced by this country, and to formulate policy alternatives in achieving sustainable Indonesian food security toward 2025. This analysis found out that in the last five years Indonesia was able to provide enough food to fulfill its people’s need, however quality of food consumption of an average Indonesian was under standard dietary pattern recommended by nutritionists. Challenges to achieve sustainable Indonesian food security toward 2025 will be more difficult. To response to the challenges, this article recommends some adjustment on policy direction of food security development, especially related to defining goals, choosing means and ways in achieving the goals, and setting targets of food security development. IndonesianPermasalahan dan tantangan untuk mewujudkan ketahanan pangan Indonesia berkelanjutan bersifat multidimensi, mencakup aspek ekonomi, sosial, politik, dan lingkungan. Indentifikasi permasalahan dan tantangan tersebut dapat dilakukan melalui analisis penawaran dan permintaan pangan. Dari sisi penawaran, tantangan tersebut diantaranya berupa persaingan pemanfaatan sumber daya alam, dampak perubahan iklim global, dan dominasi usahatani skala kecil. Dari sisi permintaan, diantara tantangan tersebut adalah pertumbuhan penduduk yang tinggi beserta dinamika karakteristik demografisnya, perubahan selera konsumen, dan persaingan permintaan komoditas pangan untuk konsumsi manusia, pakan, dan bahan baku energi. Penulisan artikel ini bertujuan untuk menganalisis kondisi ketahanan pangan Indonesia saat ini, mengkaji tantangan 10 tahun yang akan datang, dan merumuskan alternatif kebijakan untuk mewujudkan ketahanan pangan Indonesia berkelanjutan menuju 2025. Dari hasil kajian ini dapat disimpulkan bahwa selama lima tahun terakhir secara makro Indonesia mampu menyediakan pangan yang cukup untuk memenuhi kebutuhan warganya, namun kualitas konsumsi pangan rata-rata masyarakat Indonesia masih di bawah rekomendasi para ahli gizi. Tantangan menuju ketahanan pangan Indonesia berkelanjutan tahun 2025 akan semakin berat. Untuk mengatasi tantangan tersebut, dalam artikel ini disarankan perlunya dilakukan penyesuaian arah kebijakan pembangunan ketahanan pangan, khususnya dalam menetapkan tujuan, memilih cara mencapai tujuan, dan menentukan sasaran ketahanan pangan nasional.